O slovarskem delu monografije Hildegard Striedter Temps Deustsche Lehnwörter im Slovenischen - Štavbar, Simona (Slavistična revija, 2013)
The article describes the pilot project of digitalization of loanword dictionaries that includes the digitalization of the dictionary part of the monograph Deutsche Lehnwörter im Slovenischen by Hildegard Striedter-Temps. It describes the characteristics of the printed dictionary part of the monograph. The dictionary has a specific composition as it is a compilation of secondary sources that are included and organized in dictionary entries. The author's contribution is mainly in commenting on the language data and correcting erroneous etymological and other explanations by other authors. The article briefly describes the technical background of the digitalization process which included partial manual digitalization of the dictionary list of lemmata.
Keywords: "Deutsche Lehnwörter im Slovenischen"; dictionaries; digitalizacija; digitalization; digitization; etimologija; etymology; German; German langauge; leksikografija; lexicography; loanwords; nemščina; obrnjeni slovarji; prevzete besede; reverse dictionary; slovarji; Slovene; Slovene languge; slovenščina; Striedter-Temps, Hildegard